Keterlibatan Pekerjaan, Keinginan Karyawan Untuk Keluar Dan Komitmennya Pada Organisasi UKM Jasa Klinik Kecantikan Di Surabaya - Tri Siwi Agustina (Sekolah Tinggi Ilmu Ekonomi STEMBI Bandung, 2014)
Nowadays, the rapid growth of service companies, especially in beauty service area can induce competition among business subjects. Not only focusing on how to attract consumers, but also how to plan and develop human resources. By knowing employee’s involvement level they felt, the business doers on beauty services are eager to know how it can influence to reach company’s goals. This research aims for knowing the influence of employee involvement that employee feels and the effect towards employee, whether it is directly or not through organization commitment as an intervening variable. The level of employee’s intention to quit are considered important. The high turn-over rate is the big problem that avoided by companies because not only it is destructive, but also companies should ask about employees commitment that indirectly influence intention to quit. The objects of this research are front officers and beauty therapists at Natasha beauty clinic in Surabaya. After spreading 74 self-report questionnaire, 67 questionnaires were collected as a personal statement of each employee. Collected questionnaires then are processed and examined using path analysis technique. The result of the research through path analysis model proved both hypothesis examination that front officers and beauty therapists Natasha beauty clinic in Surabaya have high working involvement so that directly and negatively influence significant towards intention to quit with path coefficient level -0,29 and CR -2,634 and also P ≤ 0,05. While the indirect influence of the organization commitment as an intermediary variable results in smaller path coefficient level on -0,143. It means that the influence of increased employee’s involvement level can directly decrease intention to quit by front officers and beauty therapist in Natasha Beauty Clinic in Surabaya. This is without influenced by employee’s high organization commitment level